An image‐based small‐molecule screen identifies vimentin as a pharmacologically relevant target of simvastatin in cancer cells. Issue 5 (18th January 2018) - Trogden, Kathryn P.; Battaglia, Rachel A.; Kabiraj, Parijat; Madden, Victoria J.; Herrmann, Harald; Snider, Natasha T.
Abstract : Vimentin is a cytoskeletal intermediate filament protein that is expressed in mesenchymal cells and cancer cells during the epithelial‐mesenchymal transition. The goal of this study was to identify vimentin‐targeting small molecules by using the Tocriscreen library of 1120 biochemically active compounds. We monitored vimentin filament reorganization and bundling in adrenal carcinoma SW13 vimentin‐positive (SW13‐vim + ) cells via indirect immunofluorescence. The screen identified 18 pharmacologically diverse hits that included 2 statins—simvastatin and mevastatin. Simvastatin induced vimentin reorganization within 15–30 min and significant perinuclear bundling within 60 min (IC50 = 6.7 nM). Early filament reorganization coincided with increased vimentin solubility. Mevastatin produced similar effects at >1 μM, whereas the structurally related pravastatin and lovastatin did not affect vimentin. In vitro vimentin filament assembly assays revealed a direct targeting mechanism, as determined biochemically and by electron microscopy. In SW13‐vim + cells, simvastatin, but not pravastatin, reduced total cell numbers (IC50 = 48.1 nM) and promoted apoptosis after 24 h. In contrast, SW13‐vim − cell viability was unaffected by simvastatin, unless vimentin was ectopically expressed. Simvastatin similarly targeted vimentin filaments and induced cell death in MDA‐MB‐231 (vim + ), but lacked effect in MCF7 (vim − ) breast cancer cells. In conclusion, this study identified vimentin as a direct molecular target that mediates simvastatin‐induced cell death in 2 different cancer cell lines.—Trogden, K. P., Battaglia, R. A., Kabiraj, P., Madden, V. J., Herrmann, H., Snider, N. T. An image‐based small‐molecule screen identifies vimentin as a pharmacologically relevant target of simvastatin in cancer cells. FASEB J. 32, 2841–2854 (2018). www.fasebj.org